Early‐season brown trout (Salmo trutta) migrants grow and survive better at sea. Issue 6 (16th April 2022) - Jensen, Arne J.; Diserud, Ola H.; Finstad, Bengt; Fiske, Peder; Thorstad, Eva B.
Abstract: The timing of seaward migration is a key life‐history trait for many anadromous fish species, with growth and survival at sea depending on a match/mismatch scenario between the timing of the sea entry and optimal conditions. Based on a 25‐year study with 15, 226 individually tagged brown trout ( Salmo trutta ) in a Norwegian river, we analysed how the within‐season timing of sea migration impacted growth and survival. In both first‐time and veteran migrants, marine growth was highest for early migrating individuals, large individuals, and those with a low condition factor when entering the sea. Survival was highest for individuals entering the sea early in the season. In first‐time migrants, survival increased with body length. Survival also increased with the number of other smolts migrating simultaneously. As the early smolts were the most successful, it may seem strange that many smolts migrate later in the season. We suggest that late‐migrating smolts may not be of a size and/or physiological state suitable for early marine conditions, and may make the best of a bad situation.